Hubungan Intensitas Penggunaan Media Sosial Tiktok dengan Perkembangan Psikososial pada Anak Usia Sekolah SDN 20 Indarung - Metha Kemala Rahayu; Maidawilis Maidawilis; Yanti Nopita; Rosmi Eni (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
The psychosocial development of children at school age shows that children acquire various skills and abilities. The initial survey conducted by the author on January 2 2024, by interviewing 10 students of class IV, V, VI at SDN 20 Indarung for psychosocial development data, showed that 7 out of 9 people said they did not want to do assignments, did not want to study at home and 2 out of 9 People say they are angry if their cellphone is confiscated by their parents or teachers. And when conducting interviews to ascertain whether the students had the TikTok application and the results were obtained that 9 out of 10 of the students had and used the TikTok application for more than 3 hours a day. This type of research is quantitative research. The design of this research is analytical descriptive using a Cross Sectional Study approach. The research period was from March-April 2024. The population in this study was class IV, V, VI at SDN 20 Indarung, totaling 86 people. The results of the research can be seen that more than half of the respondents (62.8%) with sufficient psychosocial development at SDN 20 Indarung classes IV, V, VI in 2024. More than half of the respondents (59.3%) with frequent TikTok usage intensity at SDN 20 Indarung class IV, V, VI in 2024. The results showed that the proportion of poor psychosocial development was higher in the intensity of frequent TikTok use (12.8%) compared to the intensity of infrequent TikTok use (10.5%). The results of statistical tests using the chi square test obtained a value of p=0.0019 (p<0.05), meaning that there is a relationship between the intensity of TikTok use and psychosocial development at SDN 20 Indarung classes IV, V, VI in 2024.